2000
DOI: 10.1002/1099-1085(20001230)14:18<3309::aid-hyp200>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The importance of light and photoperiod in sexual reproduction and geographical distribution in the green snow alga,Chloromonas sp.-D (Chlorophyceae, Volvocales)

Abstract: The effects of premating light regimes on sexual reproduction and the production of spherical cells in Chloromonas sp.-D, a unicellular green snow alga, were studied using cross-mating strains 582C and 582D isolated from snowpacks associated with mixed hardwood-softwood forests in Whetstone Gulf State Park, Tughill Plateau, NY. Two preacclimation regimes were used, Vita-Lite as controls (530-700 nm peak) and blue light as experimentals (430-460 nm peak) prior to the mating experiments. In blue light, an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Swimming cell packs with flagella extending beyond the cell wall (Fig. 13) were very occasionally observed in the present cultures, as in all Chloromonas species in subclade 2 of clade A (Hoham et al, 2000(Hoham et al, , 2006. TEM did not reveal morphological differences between the two strains.…”
Section: Culture Strains Of Biflagellate Volvocaleans From Snow Samplessupporting
confidence: 56%
“…Swimming cell packs with flagella extending beyond the cell wall (Fig. 13) were very occasionally observed in the present cultures, as in all Chloromonas species in subclade 2 of clade A (Hoham et al, 2000(Hoham et al, , 2006. TEM did not reveal morphological differences between the two strains.…”
Section: Culture Strains Of Biflagellate Volvocaleans From Snow Samplessupporting
confidence: 56%
“…Previous studies have shown that blue wavelengths of light promoted sexual reproduction in the green snow algae Chloromonas sp., which are near relatives of Haematococcus (Hoham et al. ). Therefore, it could be speculated that blue LED wavelength put the Haematococcus cells in a stress condition that triggered sexual reproduction in them.…”
Section: Resultsmentioning
confidence: 99%
“…pichinchae (Hoham 1975) retained their flagella on parental cells at the time of cell pack formation (cell pack is used here instead of zoosporangia or gametangia because it is not possible to distinguish zoospores from gametes when cell divisions occur). Chloromonas sp.‐D has a unique cell transformation from oblong to spherical during sexual reproduction, and the number of transformed cells increases under extended photoperiods of more than 20 h of light (Hoham et al 2000, Hoham and Duval 2001). Whereas the position of Cr.…”
Section: Discussionmentioning
confidence: 99%